Improving the Method of Assessing the Efficiency of Strategic Management in Textile Enterprises (Eurasian Journal of History, Geography and Economics, 2023)
This article examines the issues of improving the technology of strategic management of textile enterprises in an innovative economy based on the selection and expansion of the stages of modern management support.